Development opportunities of basic skills of unemployed in the context of a lifelong education - Laskova, Jelena; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the qualitative aims of the lifelong education strategy is to increase proportion of people aged 25 to 64 involved in lifelong education. Involvement of unemployed into employment measures is being implemented in compliance with available resources but basic skills of people are not evaluated. In order to increase effectiveness of educational measures, it is necessary to evaluate interests, basic skills, competences, values, career tendencies of unemployed before studies so as to decrease possibilities of mistakes in choice of the courses. The aim of the article: to evaluate basic skills of unemployed in the context of lifelong education and to determine their development opportunities. The research methods used: theoretical - analysis of literature and documentation; empirical: questionnaire. Methods of data processing: analysis if statistic data, the Mann-Whitney U test. Basis of the research: 238 unemployed and job seekers in the regions of Latgale and Zemgale. Respondents are customers of State Employment Agency and social services. The research about basic skills of unemployed and job seekers gives evidence of a low selfesteem, necessity to inform about opportunities to educate and a result where the acquired knowledge can be used.